2010
DOI: 10.1039/c0dt00068j
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity and coordination modes of copper(ii) complexes of Schiff base-derived coumarin ligands

Abstract: The coordination modes of copper(II) complexes of Schiff base-derived coumarin ligands, which had previously shown good anti-Candida activity, were investigated by pH-potentiometric and UV-Vis spectroscopic methods. These studies confirmed the coordination mode of the ligands to be through the N of the imine and deprotonated phenol of the coumarin-derived ligand in solution. In addition, the more active complexes and their corresponding ligands were investigated in the presence of copper(II) in liquid and froz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 34 publications
0
46
0
2
Order By: Relevance
“…Schiff bases play an important role in biological [1][2][3] and coordination chemistry [4][5][6]. Recently, we have reported the crystal structures of afew Schiff bases and their complexes with metal atoms [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Schiff bases play an important role in biological [1][2][3] and coordination chemistry [4][5][6]. Recently, we have reported the crystal structures of afew Schiff bases and their complexes with metal atoms [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Their in vitro effects are clearly expressed . Recently, Creaven et al reported the antibacterial and anticancer activities, coordination modes of copper(II) complexes of Schiff based-derived coumarin ligands (Creaven et al, 2010). Therefore, these coumarin-metal compounds have potential to develop as anticancer drugs, which provides hope for the pursuit of non-platinum anticancer drugs.…”
Section: Other Tcm Active Ingredient-metal Based Anticancer Agents 2mentioning
confidence: 99%
“…In recent years, the successful development of metalbased pharmaceuticals, including copper anticancer agents, has attracted more attention on metal complexes in cancer treatment (1)(2)(3). Studies have shown that the copper complexes, such as dithiocarbamate (4,5), 8-hydroxyquinoline (6), clioquinol (7) and some Schiff base copper coordination compounds (8)(9)(10), exert promising anticancer activity by targeting the ubiquitinproteasome pathway (UPP) in preclinical trials.…”
Section: Introductionmentioning
confidence: 99%